Exploring the connection between critical zone structure and tree distribution in a semiarid eroding landscape with shallow seismic refraction - B. A. Flinchum; D. Hagan; C. J. Harman (Vadose Zone Journal)
Abstract This study explores the impact of deep (5–40 m) critical zone (CZ) structure on vegetation distribution in a semiarid snow‐dominated climate. Utilizing seismic refraction surveys, we identified a significant negative correlation between seismically derived saprolite thickness and light detecting and ranging‐derived vegetation heights (R = −0.66). We argue that CZ structure, specifically shallow fractured bedrock under valley bottoms, provides moisture near the surface where trees are established—suggesting the trees are situated in locations with access to nutrients and water. This work provides a unique spatially exhaustive perspective and adds to growing evidence that in addition to other factors such as slope, aspect, and climate, deep CZ structure plays a vital role in ecosystem development.